Emergency management of children with severe sepsis in the United Kingdom: the results of the Paediatric Intensive Care Society sepsis audit. Issue 5 (8th January 2009) - Inwald, D P; Tasker, R C; Peters, M J; Nadel, S
Abstract : Objective: To audit current UK practice of the management of severe sepsis in children against the 2002 American College of Critical Care Medicine/Pediatric Advanced Life Support (ACCM-PALS) guideline. Design: Prospective observational study. Setting: 17 UK paediatric intensive care units (PICUs) and two UK PICU transport services. Participants: 200 children accepted for PICU admission within 12 h of arrival in hospital, whether or not successfully transported to a PICU, with a discharge diagnosis of sepsis or suspected sepsis. Main outcome measures: Medical interventions, physiological and laboratory data to determine the presence or absence of shock, inter-hospital transfer times, predicted mortality (using the Paediatric Index of Mortality, version 2 (PIM2) scoring system) and observed mortality. Results: 34/200 (17%) children died following referral. Although children defined as being in shock received significantly more fluid (p<0.001) than those who were not in shock, overall fluid and inotrope management suggested by the 2002 ACCM-PALS guideline was not followed in 62% of shocked children. Binary logistic regression analysis demonstrated that the odds ratio for death, if shock was present at PICU admission, was 3.8 (95% CI 1.4 to 10.2, p = 0.008). Conclusions: The presence of shock at PICU admission is associated with an increased risk of death. Despite clear consensus guidelines for the emergency management of children with severe sepsis and septic shock, most children received inadequate fluid resuscitation and inotropic support in the crucial few hours following presentation.